(untitled) (International Journal of Engineering and Computer Science, 2013)
Network coding is a phenomenon which allows each node in a network to perform some kind of computation. The data sent on a node’s output link can be some function or combination of data that arrived earlier on the node’s input links. In another, network coding is the transmission, mixing, and remixing of messages arriving at nodes inside the network, such that the transmitted data can be unmixed at their final destinations or at sink. In this paper we take multiple sources which have the capacity of transmitting the data to the next intermediate node. The process of mixing operation is carried out at the intermediate node or the router. The paper also reduces the frequency of mixing the data from different source node by maintaining a fixed random function. At last the sink decodes the mixed data from different sources and reassembles to form the original data.